Pengaruh Pencampuran Metanol dalam Bahan Bakar Pertalite Terhadap Performa Mesin Sepeda Motor - Syamsul Maarif; Hedi, Hedi; Sri Widarti (SURYA TEKNIKA, 2024)
The purpose of this research is to study the effect of mixing pertalite fuel with methanol on torque, power, and fuel consumption, as well as to study the effect of mixing pertalite fuel with methanol on vehicle exhaust emissions and determine the mixture of pertalite and methanol that produces the best engine performance. Fuel variations pertalite, pertalite methanol 5% (M5), pertalite methanol 10% (M10), pertalite methanol 15% (M15), pertalite methanol 20% (M20). This test is carried out with dynotest testing which aims to determine the value of torque and power. Fuel consumption testing was carried out using the road test method, while testing exhaust emissions using Gaz Analyzer. In testing using dynotest, it can be seen that the addition of methanol makes the torque value produced greater, the highest torque value is produced by M20 fuel which is 22.37 Nm. The highest power value is produced by M20 fuel, which is 13.2 Hp. The results of fuel consumption testing with the road test method using pertalite, M5, M10, M15, M20 fuels with the same amount of fuel, namely 250 ml, show that M20 fuel produces the least fuel consumption value of 0.018 l/km with the longest mileage compared to other fuels, namely 13.2 km. The results of HC, CO and CO₂ exhaust emissions testing show that M20 fuel produces the least HC, CO and CO₂ exhaust emissions compared to other fuels.